Increased the Intensity of Elderly Visit to Posyandu with Family Support - Desi Sandra Fatmawati; Edy Soesanto (South East Asia Nursing Research, 2019)
The decline in health, especially in the elderly will affect the independence and quality of life of the elderly. The role of the family is needed to motivate the elderly in health checks to health services. One of the health services for the elderly is the elderly Posyandu which is an integrated health service for the community-based elderly. Based on data the level of elderly visits to Posyandu the elderly shows that the level of elderly visits to the Posyandu of the elderly is relatively low. The low number of elderly visits to Posyandu is influenced by several factors, one of them is the support from the family. The low number of elderly visits to Posyandu is influenced by several factors, one of them is the support from the family. The purpose of the research was to found out the relationship between family support and the intensity of elderly visits to PosyanduSumber Sehat. This research used a quantitative descriptive correlational study with a cross-sectional design. The sample in this study was 82 elderly respondents with a purposive sampling technique. The results showed that good family support was 46 (56,1%) and less family support was 36 (43,9%). The intensity of elderly visits in the low category was 48 (58.5%) and there were 34 (41.5%) with high visit intensity. There was a significant relationship between family support and the intensity of elderly visits to posyandu.